An Investigation of Soil Profile Depth Change on Site Response Analysis - Fatma İlknur KARA; Barış Şahin (Doğal Afetler ve Çevre Dergisi)
The updated Turkish seismic code “Building Earthquake Regulations-2018 (TBDY-2018)” includes radical changes in many aspects such as peer review and the earthquake hazard map hence, it brings new conditions into practical engineering. One of the most important conditions is the concept of "Site Response Analysis" for the soil type “ZF”. This study investigates the item 16.5.2.3 (a) which states that “the depth of the engineering bedrock from the building foundation must not be less than three times of the largest building width. However, the application of this provision is almost difficult especially for the large span structures, and it requires additional cost. In this context, the soil profile evaluation has been made within the borders of Konak district of İzmir province for soil class "ZF" considering four different depths. Non-linear bidirectional time history analyses are performed using 11 pairs of earthquake records which are scaled to match various earthquake levels. The study also evaluates the effect of various depths on the behavior of the soil profile in question. The paper concludes that, for the soil profile addressed in this study, the derived design spectrum related to soil type ZE- regardless of the depth change - is conservative for all periods except the high rise buildings as well as the buildings that do not require advanced performance evaluations such as new designed reinforced concrete buildings, precast concrete buildings and steel buildings.